The effect of an exercise program in water on pain level and functional status in chronic nonspecific low back pain patients: A single-blind randomised controlled trial - Ester Goldstein; Ella Shoval; Nira Koren-Morag (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Background: Lower back pain is one of the most widespread health issues today. Water-based exercise is an effective treatment to reduce pain intensity and disability. Objective: To assess the effect of a water exercise program on pain level and functional status in patients suffering from chronic nonspecific low back pain.  Methods: One hundred and twenty-four volunteers with chronic nonspecific low back pain, aged 19 to 70, were randomly assigned to either a water exercise group or a land exercise group. Both groups performed exercises that combined local deep muscles transversus abdominis and the multifidus with diaphragm activity, with the integration of movements of routine daily life. Both programs lasted three months, with twice-weekly sessions of 45-minutes each.  Results: Significantly better improvement of all pain variables and functional status was found in the water group. The major significant (p<0.001) contribution of the water group was obtained for pain description improvement. A multivariate linear regression model examined the predictors for pain and functional status improvement.  Conclusions: The water program has a greater potential than the land program for pain reduction and improving functional status of patients with chronic nonspecific low back pain.